Redesain lanskap Jalan Kiai Haji Hasyim Asy’ari Kabupaten Tulungagung, Jawa Timur berkonsep arsitektur humanistik - Kukuh Mukti Ginayuh; Anak Agung Gede Sugianthara; I Made Agus Dharmadiatmika (Prodi Arsitektur Lanskap, Fakultas Pertanian, Universitas Udayana, 2025)
K.H. Hasyim Asy'ari as the only road segment that has a median in Tulungagung Regency does not yet have an arrangement that is in accordance with road landscape guidelines in Indonesia. This affects the beauty of the road landscape as well as the comfort and safety of road users. Based on these problems, this study aims to determine the development of landscape potential and create a landscape design for Jalan K.H. Hasyim Asy'ari, Tulungagung Regency. This study uses a survey method, with data collection techniques through literature study, observation, and interviews. The design plan for this road landscape refers to government regulations, adopting local culture, such as adding Reog Kendang statue ornaments placed at the beginning and end of the median and the pedestrian lamp post design that transforms the typical batik motif of Tulungagung. Determination of plants is carried out to create a design that is safe, does not endanger road users, is comfortable, and beautiful, it must take into account various considerations such as ecological conditions, plant groups, plant forms, plant age, and plant criteria. The landscape design recommendations are expected to be input for the Tulungagung Regency government to develop road landscapes as green open space for roads.